Karakteristik Fisikokimia dan Mikrobiologi Permen Jeli Jahe (Zingiber officinale) terhadap Daya Simpan dengan Teknik Pengemasan Berbeda - Muh. Doddy Pratama; Pratiwi Jati Palupi; Retno Prasetia; M. Muhtar (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2021)
Jelly candy is one type of candy that has basic composition such as granulated sugar (glucose/sucrose), gelatin (jelly base), and additional organic ingredients like Ginger which can use as preservative and naturally flavor. In the Ginger jelly candy production, Packaging is one of main evaluation to protect the quality of product. The study was carried out to know effect of difference of Packaging Technique on physical-chemical characterization and microbiology correlate to storability of ginger jelly candy. Physical characterization (organoleptic) on flavor, taste, texture and color were evaluated by Hedonic test through questionnaire, chemical characterization including moisture content and sugar content were analyzed by Gravimeter and Refractometer method, and bacterial contaminations figures was analyzed by total plate count method. The result showed packaging technique was no effect on organoleptic characterization and Sugar Content but it was effect on moisture content and bacterial contamination figures of ginger jelly candy. Storability was effect on organoleptic, moisture and sugar content, and bacterial contaminations figures. Non vacuum was higher compared to vacuum of packaging technique on moisture content and bacterial contaminations figures (43.01 % and 46 cfu/g, 23.38 % and 29 cfu/g (0 week)), (48.45% and 300 cfu/g, 43.48% and 71 cfu/g (4 week)) respectively.